Organizational prosperity under inner marketing orders - Rasha F Mustafa (Research Parks Publishers, 2023)
The current study aims to test the impact of the organizational prosperity of inner marketing at the University of Baghdad in Baghdad Governorate, to identify its results and realize what must be done to improve internal marketing, and based on the most important research topic, the imaginary ongoing research organization, and the options available for descriptive analysis in completing this study, it is based on the questionnaire tool as an investigation tool for data related to the research variables, their dimensions, and paragraphs in addition to supporting it with structured interviews to diagnose the research problem, to analyze the primary data through descriptive statistics (arithmetic mean, standard deviation, coefficient of variation, percentages, frequencies), test hypotheses using appropriate statistical methods for inferential statistical analysis, simple linear regression, multiple regression, path analysis) and verify the quality of the data. Through normal distribution, confirmatory factor analysis, structural modeling method, and exploratory factor analysis), after collecting data from (252) observations of university leaders, the sample was a random sample of a population that included leaders of employees at the University of Baghdad. the current study used a number of statistical methods via (26) SPSS program and (9.25 AMOS) program. The statistical analysis concluded the most prominent result was the impact of organizational prosperity directly on inner marketing, and indirectly through.